1
$\begingroup$

I've been working on this problem for the last 45 minutes, and I keep getting the wrong answer, no matter what I do. I tried squaring the whole equation, so that there was no radical to deal with - didn't work. I tried the product rule + chain rule - didn't work. Is anyone able to explain how to do it? I'm really desperate.

Thank you so much!

$\endgroup$
  • $\begingroup$ Hint: You may begin by noting that $$\sqrt{x^2+y^2}=15\qquad\iff\qquad x^2+y^2=225$$ $\endgroup$ – Ángel Mario Gallegos Nov 3 '15 at 3:14
2
$\begingroup$

$$(x^2+y^2)^\frac 12 = 15$$ differentiating ... $$(x^2+y^2)^{-\frac 12}(2x+2yy') = 0$$ clearly only the second factor can be zero so

$$y'=-\frac xy $$

as required for a circle (slope of tangent is the negative reciprocal of the slope of the radius )

$\endgroup$
  • $\begingroup$ I thought the expression is $y (x^2+y^2)^\frac 12 = 15$ $\endgroup$ – ja72 Nov 3 '15 at 6:39
  • $\begingroup$ @ja72 The question was changed after I posted my answer $\endgroup$ – WW1 Nov 3 '15 at 6:44
2
$\begingroup$

Assume $y(x)$ is a function of $x$ on an open domain around $(x_0,y_0)$, then: $$ 0=\left(y(x)\sqrt{y(x)^2+x^2}-15\right)'=y'(x)\sqrt{y(x)^2+x^2}+y(x)\frac{y(x)y'(x)+x}{\sqrt{y(x)^2+x^2}}\Leftrightarrow $$ $$ 0=y'(x)\left(2y(x)^2+x^2\right)+xy(x)\Rightarrow y'(x)=-\frac{xy(x)}{2y(x)^2+x^2} $$ Meaning: $$ y'=-\frac{xy(x)}{2y^2+x^2} $$

$\endgroup$
1
$\begingroup$

You have $f(x,y)=C$ and apply the chain rule

$$ \frac{\partial f(x,y)}{\partial x} {\rm d}x + \frac{\partial f(x,y)}{\partial y} {\rm d} y = 0 $$

In your case

$$ \frac{x y}{\sqrt{x^2+y^2}} {\rm d}x + \frac{x^2+2 y^2}{\sqrt{x^2+y^2}} {\rm d} y = 0 $$

$$ \frac{{\rm d}y}{{\rm d}x} = - \frac{x y}{x^2+2 y^2} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.